Unsystematic factors leading to the poorer performance of the six listed banks in Singapore in1998 compared with 1997 - Ong, Siew Mui. (2008)
The unsystematic factors that had led to the poorer performance of the six listed banks in Singapore in 1998 compared with 1997 includes the hefty provisions made for possible loan losses due to greater regional exposure and higher operating expenses. DBS was the worst performer, in terms of earnings per share (EPS) whereas UOB had the highest EPS in 1998.